New Prognostic Biomarkers and Drug Targets for Skin Cutaneous Melanoma via Comprehensive Bioinformatic Analysis and Validation - Zhou, Sitong; Han, Yuanyuan; Li, Jiehua; Pi, Xiaobing; Lyu, Jin; Xiang, Shijian; Zhou, Xinzhu; Chen, Xiaodong; Wang, Zhengguang; Yang, Ronghua (Frontiers in Oncology, 2021)
Objective: Skin Cutaneous Melanoma (SKCM) is the most dangerous type of skin cancer and has highly heterogeneous features. There is an urgent need to identify markers for early diagnosis and therapy. A detailed profiles of them are meaningful to assess their malignant potential and treatment usage. Here, we constructed a co-expression module using the expression data of cutaneous melanoma. Methods: A specific co-expression gene module for the pathogenesis of this disease was discovered. We further conducted a comprehensive bioinformatic analysis on selected hub genes. Additionally, The Connectivity Map (CMAP) was used to predict drugs for the treatment of SKCM based on hub genes. Immunohistochemical (IHC) staining was performed for validation in protein level. Results: Combined with GWAS validation and DEGs analysis intersection on the modules of interest, we determined 10 hub genes in the most relevant module. Survival curves indicated that 8 hub genes were significantly negatively associated with the OS. A total of 8 hub genes were positively correlated with SKCM tumor purity and 10 hub genes were negatively correlated with the infiltration level of CD4 + T cells and B cells. The methylation levels of 7 hub genes in SKCM stage 2 were significantly lower than stage 3. We also analyzed the isomer expression level of 10 hub genes to explore the therapeutic target value of 10 hub genes in terms of AS. All of 10 hub genes have mutations in skin tissue. Furthermore, CMap analysis screened out four targeted therapy drugs (cefamandole, ursolic acid, podophyllotoxin, and Gly-His-Lys) that may be effective treatments for SKCM. Finally, the IHC staining results showed that all ten molecules all highly expressed in melanoma specimens. Conclusion: These findings may provide new insight into SKCM pathogenesis based on multi-omics profiles of key prognostic biomarkers and drug targets. GPR143 and SLC45A2 was related to immune microenviroment, which may serve as a drug targets for immunotherapy and prognostic biomarker for SKCM. Meanwhile, four drugs were also identified with significant potentiality in treating SKCM patients.